Effect of Seaweed Extract (Sargassum wightii) on Seedling Growth Promotion in the Long Bean (Vigna unguiculata) Hawari verity - Gamage, G.C.T.; Sathees, D.; Hemalatha, J.P.S. (Uwa Wellassa University, 2021)
Growth in the human population urges the need for increment in food production. This leads to indiscriminate use of synthetic and chemicals for their agricultural lands resulting are highly toxic to the environment and soil. Our study aims to develop a seaweed extract from commonly available seaweed Sargassum wightii to enhance the plant growth promotion in the Hawari verity Long bean (Vigna unguiculata). The seaweed extract was treated at six different levels of T1 – 0%, T2 – 5%, T3 – 10%, T4 – 15%, T5 – 20%, and T6 –25% for long bean Hawari verity. The extraction was used to check the seed germination percentage and shoot length, root length, the number of leaves was measured at 4th, 8th, 12th and 16th days after transplanting. The highest seed germination percentage of 94.44% was observed in T4 whereas the lowest of 56.64% was observed in T6. The highest shoot length of the seedling was observed in T5 and lowest in T1. Similarly, the highest root length (7.07±0.42 cm) was observed in T5 and the lowest (6.00±0.51cm) in T1 on the 16th day. The highest (6.46±0.51) and lowest (5.46±0.51) number of leaves were observed in T5 and T1. The results suggest that 20% Sargassum wightii extract enhances the germination and growth of Hawari verity seedling on Vigna unguiculata. Sargassum wightii extract can be used in organic agriculture.
Keywords: Long bean; Organic fertilizer; Sea weed extract; Seed germination; Seedling growth